A REVISÃO CONTRATUAL E O PRINCÀPIO DA ONEROSIDADE EXCESSIVA SUPERVENIENTE FRENTE À€ COVID-19 (CIPEEX, 2022)
IS IT POSSIBLE TO REVISE BUSINESS CONTRACTS VIS--VIS COVID-2019, BASED ON THE PRINCIPLE OF SUPERVENING EXCESSIVE BURDEN? IT WAS SHOWN THAT IT IS POSSIBLE TO REVISE THE BUSINESS CONTRACTS VIS--VIS COVID-2019, BASED ON THE PRINCIPLE OF SUPERVENING EXCESSIVE COST. THE SARS-COV-2 PANDEMIC, WHICH IS AN ABBREVIATION FOR CORONA VIRUS DISEASE (€ŒDISEASE CAUSED BY THE CORONA VIRUS€, LITERALLY TRANSLATED FROM ENGLISH) CORONAVIRUS, KNOWN WORLDWIDE AS COVID-19, WAS CHARACTERIZED AS AN EXTRAORDINARY AND UNPREDICTABLE EVENT, WHICH MAKES THE RELATIONSHIP BETWEEN THE PROVISION AND THE TAKING OF SERVICES BECOME EXCESSIVELY BURDENSOME. THE DEDUCTIVE METHOD WAS USED IN ORDER TO ANALYZE HOW THE LAW DISCIPLINES THE REVIEW OF BUSINESS CONTRACTS BY COMPANIES FINANCIALLY AFFECTED BY COVID-19, WITH THE OBJECTIVE OF KNOWING MAINLY HOW TO CARRY OUT SUCH REVIEW, FOR THE PRESERVATION OF THE COMPANIES AFFECTED IN BRAZIL. THERE ARE SEVERAL CONCEPTS THAT, OVER TIME, WERE GIVEN TO THE CONTRACTUAL REVIEW, AND THEIR ORIGINS ARE VARIED, AS WELL AS THE LEGAL PRECEPTS GUIDING SUCH A LEGAL INSTITUTE REGARDING BUSINESS CONTRACTS SPECIFICALLY. THUS, IT WAS CONCLUDED THAT, THE CONTRACTUAL REVIEW THROUGH THE JUDICIAL ROUTE IS POSSIBLE, THROUGH THE FULFILLMENT OF THE REQUIREMENTS LISTED IN THE BRAZILIAN LEGISLATION, HOWEVER, THE BEST ROUTE THAT THE ENTREPRENEUR CAN CHOOSE, IS THE EXTRAJUDICIAL, BECAUSE IN THIS WAY, HE WILL BE SAVING SUCCUMBENTIAL EXPENSES. AND MAINTAINING THE COMMERCIAL RELATIONSHIP.
Keywords: Contract Review; Excessive Onerosity; COVID-2019